(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
One of the main problems of the national economy is to determine how to use the potential of the existing ecosystem structure and how much is intact to create additional services in this ecosystem in the future. Before society can decide how to answer this question, it needs to have a good understanding of the nature of the unique natural resources available in this ecosystem, along with prioritizing higher goals. Food production relies on biodiversity for a variety of food plants, pollination, pest control, nutrient supply, genetic diversity, and disease prevention and control.